Modified Zakharov–Kuznetsov equation posed on a strip. Issue 2 (22nd January 2022) - Castelli, M.; Doronin, G.
ABSTRACT: An initial-boundary value problem of Saut–Temam type for the modified Zakharov–Kuznetsov equation posed on a strip is considered. Critical power in nonlinearity has been studied. The results on existence, uniqueness and asymptotic behavior of solutions are presented.